An exploratory study on the perceptions and experiences the of adolescent males about gender-based violence in their families and communities - Banzana, Mihlali (Department of Social Development, 2025)
Gender-based violence (GBV) is a global phenomenon that affects many women and children across all cultures, races, and socio-economic circumstances. This phenomenon also impacts survivors' physical and psychological wellbeing as a direct result of the abuse and as the body responds to the trauma. Understanding the context in which young males recognise and view GBV is important as it will refine the effectiveness of intervention programmes so that these youths' worldview can be shifted despite the fact that society often expects that males use violence as part of conflict management in social settings. Framed through the lens of the social constructionist view of gender and the ecological systems theory, the study is aimed at understanding how socialisation takes place in families and communities play a role in shaping young men's views and perceptions about GBV. The study sampled 16 young males aged between 18 and 25 years from various townships in Gqeberha. Using the qualitative exploratory approach, a semi-structured interview schedule was utilized, leading to the rich collection of data. All interviews were transcribed manually using Microsoft Office. During data analysis, 3 major themes emerged: contributing factors of gender-based violence in the household, the effects of gender-based violence on individuals, families and communities, and proposed intervention plans. Results indicated that young males realise that GBV is a form of cruelty against humanity. Factors impacting the perpetrator including violent socialisation, violent coaching by peers, the use of substances and their emotion regulation thereby impacting their personality traits. The results further indicated that communities have accepted violence as a part of their daily lives, and this has created a despondence in efforts to reducing violence. Proposed interventions included addressing gender inequality, the establishment of supportive social systems for both perpetrators and survivors, and community education to assist in maintaining the change.